2019
DOI: 10.1186/s12934-019-1090-4
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic engineering of microorganisms for production of aromatic compounds

Abstract: Metabolic engineering has been enabling development of high performance microbial strains for the efficient production of natural and non-natural compounds from renewable non-food biomass. Even though microbial production of various chemicals has successfully been conducted and commercialized, there are still numerous chemicals and materials that await their efficient bio-based production. Aromatic chemicals, which are typically derived from benzene, toluene and xylene in petroleum industry, have been used in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
105
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(105 citation statements)
references
References 205 publications
0
105
0
Order By: Relevance
“…Microbial metabolic engineering and synthetic biology studies demonstrated that redirection of carbon flux and efficient supply of a specific primary precursor(s) are critical to achieve efficient production of downstream target products ( Fig. 1A) (16,(35)(36)(37)(38). Thus, holistic understanding and engineering of both primary and specialized metabolisms are crucial for efficient and sizable production of natural products in plants.…”
Section: Challenges To Build Plant Chassis For Synthetic Biologymentioning
confidence: 99%
“…Microbial metabolic engineering and synthetic biology studies demonstrated that redirection of carbon flux and efficient supply of a specific primary precursor(s) are critical to achieve efficient production of downstream target products ( Fig. 1A) (16,(35)(36)(37)(38). Thus, holistic understanding and engineering of both primary and specialized metabolisms are crucial for efficient and sizable production of natural products in plants.…”
Section: Challenges To Build Plant Chassis For Synthetic Biologymentioning
confidence: 99%
“…Furthermore, it is important to mention that, unlike the studies in E. coli, the precursor supply of phenylpyruvate was not modified in our strains. This is a pivotal target for further studies as usually the aromatic amino acid biosynthesis pathway in bacteria is strictly regulated and limits the precursor supply (Huccetogullari et al 2019;Lee and Wendisch 2017;Rodriguez et al 2014;Sprenger 2007). It was shown for Streptomyces venezuelae that an improved flux through the shikimate pathway by overexpressing the genes of shikimate kinase (aroK) and dehydroquinate synthase (aroB) increased the production of the aromatic antibiotic chloramphenicol (Vitayakritsirikul et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The shikimate pathway, which is confined to plastids in plants, is responsible for the synthesis of aromatic amino acids that are precursors to secondary metabolites such as pigments, alkaloids, hormones, and phenylpropanoids including lignin [9]. In microbes, the shikimate pathway has been exploited for the production of aromatic chemicals which are otherwise derived from petroleum-based benzene, toluene and xylene [10,11]. Nevertheless, most aromatic compounds used for industrial applications are still synthesized chemically Fig.…”
Section: Biochemicals Derived From the Shikimate Pathwaymentioning
confidence: 99%